Management of Character Education in the Ta'dzim Tradition : Studies in the Dayah Mudi of the Great Mosque of Samalanga: Pengelolaan Pendidikan Karakter dalam Tradisi Ta'dzim : Studi di Dayah Mudi Masjid Agung Samalanga - Ibnu Kasir (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2025)
This study aims to examine the character education management model based on the traditional Islamic boarding school (dayah) system at Dayah MUDI Mesra Samalanga, one of the largest Islamic educational institutions in Aceh. Amidst the current moral crisis among youth, pesantren play a significant role in instilling values through value-based and exemplary approaches. This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, participatory observation, and documentation. Data analysis followed the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings reveal that the character education management model at Dayah MUDI Mesra is not formally documented in a written curriculum but operates systematically through three key stages: (1) planning based on values and scholarly traditions inherited across generations, (2) implementation through role modeling, habituation, and collective supervision, and (3) evaluation through moral and spiritual guidance rather than administrative assessment. Character education is not limited to formal instruction but is embedded in the daily social and religious life of the students. This model demonstrates that value-based character education management can create a consistent and authentic moral development environment. This study recommends integrating Islamic value-based educational management principles into the development of character education curricula in formal educational institutions, drawing inspiration from the local wisdom and educational practices of pesantren.